Heparan Sulfate Proteoglycan Signaling in Tumor Microenvironment - De Pasquale, Valeria; Pavone, Luigi Michele (International journal of molecular sciences, 2020)
In the last few decades, heparan sulfate (HS) proteoglycans (HSPGs) have been an intriguing subject of study for their complex structural characteristics, their finely regulated biosynthetic machinery, and the wide range of functions they perform in living organisms from development to adulthood. From these studies, key roles of HSPGs in tumor initiation and progression have emerged, so that they are currently being explored as potential biomarkers and therapeutic targets for cancers. The multifaceted nature of HSPG structure/activity translates in their capacity to act either as inhibitors or promoters of tumor growth and invasion depending on the tumor type. Deregulation of HSPGs resulting in malignancy may be due to either their abnormal expression levels or changes in their structure and functions as a result of the altered activity of their biosynthetic or remodeling enzymes. Indeed, in the tumor microenvironment, HSPGs undergo structural alterations, through the shedding of proteoglycan ectodomain from the cell surface or the fragmentation and/or desulfation of HS chains, affecting HSPG function with significant impact on the molecular interactions between cancer cells and their microenvironment, and tumor cell behavior. Here, we overview the structural and functional features of HSPGs and their signaling in the tumor environment which contributes to tumorigenesis and cancer progression.